Decision Making Factors Among Women Delivering at Tertiary Care Hospital in Eastern Nepal - Sharma, Ismita; Kc, Heera; Mishra, Anjali (Birat Journal of Health Sciences, 2025)
Introduction: Maternal healthcare is a crucial to public health and despite notable improvements in Nepal’s access to utilization of maternal healthcare, disparities persist based on social understanding. This study aims to identify the factors influencing women’s decisions to deliver at tertiary care hospitals. Objective: The objective was to investigate the decision making factors among women’s delivering for childbirth at tertiary care hospital in the eastern part of Nepal. Methodology: This descriptive prospective cross -sectional study was conducted from November to December 2023 at Department of Obstetrics and Gynecology, Birat medical college Teaching Hospital. The study involved mothers aged 20-25 fulfilling inclusion criteria and data was collected through face-to-face interviews using a self-structured proforma, ensuring privacy and comfort. Mothers sociodemographic data and responses from the questionnaire was entered in excel sheet and calculation done by SPSS. Results: In 275 pregnant mothers, with mean age of 25.32 ± 4.54 years, majority (65.8%) resided more than an hour away from the hospital. Notably, (80.7%) were first-time hospital users. Family members primarily made the decision for hospital deliveries (65.1%). Most women(89.4%) found the reception staff approachable,99.6% reported easy access to doctors, 94.9% experienced short waiting times, and 98.9% praised the cleanliness of hospital facilities. All respondents felt respected by doctors (100%), and nearly all (99.3%) believed doctors allocated sufficient consultation time. Conclusion: The study highlight high levels of satisfaction with the care provided at the tertiary care hospital, despite challenges such as distance which reflects trust in the hospitals services.